Validation of egalitarian education questionnaire using Rasch measurement model - Nek Rakami, Nik Muhammad Hanis; Ismail, Nik Ahmad Hisham; Abu Kassim, Noor Lide; Idrus, Faizah (Journal of Applied Measurement, Press, 2020)
This paper describes the process of assessing the unidimensionality and validity of egalitarian education (EE) items based on the Rasch measurement model. Egalitarian education was measured by a self-developed 5 EE items of Likert-scale format. The process of assessing the validity of EE items involved a collection of data from 400 Malay teachers, who are teaching in government school around peninsular of Malaysia where the measurement of construct validity for the overall EE items were established using Winsteps. Various Rasch measurement tools were utilized to demonstrate the true unidimensionality and validity measure of the EE items and in meeting the needs of the Rasch measurement model. The findings show that the validity and unidimen- sionality of EE items can be truly established and can satisfy the characteristics of the Rasch measurement model.